Exploring the evolution of CHS gene family in plants - Yang, Li; Zhang, Shuai; Chu, Dake; Wang, Xumei (Frontiers in Genetics, 2024)
Chalcone synthase (CHS) is a key enzyme that catalyzes the first committed step of flavonoid biosynthetic pathway. It plays a vital role not only in maintaining plant growth and development, but also in regulating plant response to environmental hazards.However, the systematic phylogenomic analysis of CHS gene family in a wide range of plant species has not been reported yet. To fill this knowledge gap, a large-scale investigation of CHS genes was performed in 178 plant species covering green algae to dicotyledons. A total of 2,011 CHS and 293 CHS-like genes were identified and phylogenetically divided into four groups, respectively. Gene distribution patterns across the plant kingdom revealed the origin of CHS can be traced back to before the rise of algae. The gene length varied largely in different species, while the exon structure was relatively conserved. Selection pressure analysis also indicated the conserved features of CHS genes on evolutionary time scales. Moreover, our synteny analysis pinpointed that, besides genome-wide duplication and tandem duplication, lineage specific transposition events also occurred in the evolutionary trajectory of CHS gene family. This work provides novel insights into the evolution of CHS gene family and may facilitate further research to better understand the regulatory mechanism of traits relating to flavonoid biosynthesis in diverse plants.